Vocal learning in songbirds: the role of syllable order in song recognition. (25th October 2021) - Mol, Carien; Bolhuis, Johan J.; Moorman, Sanne
Abstract : Songbird vocal learning has interesting behavioural and neural parallels with speech acquisition in human infants. Zebra finch males sing one unique song that they imitate from conspecific males, and both sexes learn to recognize their father's song. Although males copy the stereotyped syllable sequence of their father's song, the role of sequential information in recognition remains unclear. Here, we investigated father's song recognition after changing the serial order of syllables (switching the middle syllables, first and last syllables, or playing all syllables in inverse order). Behavioural approach and call responses of adult male and female zebra finches to their father's versus unfamiliar songs in playback tests demonstrated significant recognition of father's song with all syllable-order manipulations. We then measured behavioural responses to normal versus inversed-order father's song. In line with our first results, the subjects did not differentiate between the two. Interestingly, when males' strength of song learning was taken into account, we found a significant correlation between song imitation scores and the approach responses to the father's song. These findings suggest that syllable sequence is not essential for recognition of father's song in zebra finches, but that it does affect responsiveness of males in proportion to the strength of vocal learning. This article is part of the theme issue 'Vocal learning in animals and humans'.